Relationship between CD-8 Expression to Treatment Response in Nasopharyngeal Carcinoma Patient After Neoadjuvant Chemotherapy in Dr. Mohammad Hoesin Hospital Palembang - Utama, Denny Satria; Eriza; Belly Sutopo Wijaya; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Nasopharyngeal carcinoma (NPC) is the most common malignancy in head and neck in Indonesia with 19,943 new cases in 2020 resulting 13,399 deaths. Lymphocytes are cells that play a role in the anti-cancer immune response, especially CD-8 T-cells. Neoadjuvant chemotherapy is chemotherapy given before radiotherapy that aims to kill primary tumors and micrometastasis tumors. This study aims to find out the relationship of CD-8 expression to treatment response in NPC undergoing neoadjuvant chemotherapy at Dr. Mohammad Hoesin Hospital Palembang. Methods. This study is an analytical observational research study on a retrospective cohort basis. Data collection from medical records using total sampling in 15 patients pilot study of NPC patients undergoing neoadjuvant chemotherapy and conducted CD-8 examination at ORLHNS polyclinic Dr. Mohammad Hoesin Hospital Palembang from December 2018 to December 2019 that met the criteria of inclusion and exclusion. Results. From 15 samples, the average CD-8 test result before neoadjuvant chemotherapy was 24.54 ng/μL and after neoadjuvant chemotherapy was 193.56 ng/μL. There was a tendency to increase the average CD-8 from before to after completion of neoadjuvan chemotherapy with a statistically significant difference of p =0.001. ROC analysis found CD-8 cut off points is 23.76 ng/μL with an area below the curve is 0.667. There were no significant relationships between CD-8 to performance status and treatment response with p values of 0.289 and 0.219, respectively. Conclusions. There was a significant change between CD-8 before neoadjuvant chemotherapy and after neoadjuvant chemotherapy with increased CD-8 tendencies and trends from before to after 6 series neoadjuvant chemotherapy with CD-8 cut off points is 23.76 ng/μL. In this study there has not been a significant relationships between CD-8 to performance status and treatment response in NPC patients undergoing neoadjuvant chemotherapy.